2022
DOI: 10.1186/s12913-022-08151-7
|View full text |Cite
|
Sign up to set email alerts
|

Contributions and challenges of healthcare financing towards universal health coverage in Ethiopia: a narrative evidence synthesis

Abstract: Background High burden of healthcare expenditure precludes the poor from access to quality healthcare services. In Ethiopia, a significant proportion of the population has faced financial catastrophe associated with the costs of healthcare services. The Ethiopian Government aims to achieve universal health coverage (UHC) by 2030; however, the Ethiopian health system is struggling with low healthcare funding and high out-of-pocket (OOP) expenditure despite the implementation of several reforms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The pooled PC, HSU, FRP, HRQoL, and HSQ, respectively, were 40.1%, 64.5%, 79.4%, 63%, and 92.1%. A narrative review also revealed that health financing initiatives contributed to income generation, risk pooling, and the acquisition of healthcare services to support the road to UHC [ 65 ]. Other evidence in Africa and Asia also showed that health insurance has been found to have an impact on resource mobilization, FRP, service utilization, quality of care, social inclusion, and community empowerment [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pooled PC, HSU, FRP, HRQoL, and HSQ, respectively, were 40.1%, 64.5%, 79.4%, 63%, and 92.1%. A narrative review also revealed that health financing initiatives contributed to income generation, risk pooling, and the acquisition of healthcare services to support the road to UHC [ 65 ]. Other evidence in Africa and Asia also showed that health insurance has been found to have an impact on resource mobilization, FRP, service utilization, quality of care, social inclusion, and community empowerment [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schemes that emphasize patients’ bargaining power at the patient-provider interface, however, appear to increase access to high-quality care [ 93 ]. In fact, Ethiopia’s CBHI had a considerable positive impact on healthcare infrastructures, medical supplies, diagnostic capacity, pharmaceuticals, FRP, and healthcare services [ 65 ]. However, the thrust of the service delivery process seems to be far behind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 68 Most of the health related millennium development goals have been achieved in Ethiopia and are considered to be attributed to a comprehensive approach to health development, including health financing and other socioeconomic systems. 69 70 Palestine is a refugee area that has received high levels of aid and a considerable amount of charitable resources per capita. 71 Even the poorest countries seem to have achieved important reductions in all cause mortality by implementing these multi-tiered strategies.…”
Section: Discussionmentioning
confidence: 99%
“…63 Additionally, the cost of vegetables is a barrier for low-income families, including those in Ethiopia, to make healthier food choices. 64 Many researchers report that, 65 people of higher socioeconomic status are more likely to have healthier food choices, while those of a lower social class have nutrient profiles that are less consistent with dietary recommendations or dietary guidelines, which contributes to their poorer state of health. For example, in Africa (Ethiopia, Eritrea, Sudan, Nigeria, and others), the root causes of malnutrition are poverty, inadequate food production, inadequate food intake, ignorance and unequal distribution of food, poor food storage techniques, improper food preparation, food restrictions and taboos and poor hygiene.…”
Section: Nutrition In Ethiopia -The Impact Of Economic Factorsmentioning
confidence: 99%